Does Corporate Governance Moderate the Relationship between Dividend Policy and Earnings Quality: Evidence from Pakistan - Atif Atique Siddiqui; Tehmina Afzal; Kamran Azam; Imran Muhammad (International Journal of Business and Economic Affairs, 2022)
This endeavour aimed to empirically investigate the moderating role of the corporate governance characteristics (board size, board independence, board meetings, CEO duality, audit quality, nomination and remuneration committee) in the dividend policy and earnings quality nexus. The study was conducted on the data consisting of 145 non-financial companies listed on Pakistan Stock Exchange (PSX) with 1450 firm-year observations for the period 2010-2019. Earnings quality was assessed by the earnings management represented by discretionary accruals which were estimated by employing the Modified jones model (1995). Multiple Panel regression model was used for analysis. It was discovered that the board size, board meetings, CEO duality and audit quality moderate the relationship between the dividend policy and earnings quality. While the board independence, nomination committee and remuneration committee, were found to have no such influence. Overall the outcomes of this research work suggest that corporate governance mechanisms deserve the attention of all the financial statements users attempting to determine the earnings quality of firms.